Il volontarismo di Guglielmo d’Ockham - Mestre, Alberto (Alpha Omega, 2015)
Summary: The article focuses on the voluntaristic doctrine of William of Ockham and his school. His philosophical and theological premises provoke consequences that change the whole view of the great moral issues. The theme of obligation arises as a core principle, changing the perspective of freedom, human acts, virtues and passions, thus transforming morality. More specifically, this produces a profound upheaval in the conformity of the human will to the Will of God, in which the fundamental aspects of this conformity are obligation, norm and obedience (always understood in the Ockhamian sense). With the doctrine of William of Ockham we are already far from the great harmonious and balanced synthesis of St. Thomas Aquinas. Key words: conformity, Will of God, Will of the Father, obedience, self-abandonment to divine will. Parole chiave: conformità, Volontà di Dio, Volontà del Padre, obbedienza, abbandono alla Volontà divina.